2021
DOI: 10.3389/fphar.2020.608707
|View full text |Cite
|
Sign up to set email alerts
|

Gastrodin Inhibits Virus Infection by Promoting the Production of Type I Interferon

Abstract: Type I interferon (IFN-I) plays a critical role in the antiviral immune response. However, viruses have developed different strategies to suppress the production of IFN-I for its own escape and amplification. Therefore, promoting the production of IFN-I is an effective strategy against virus infection. Gastrodin (GTD), a phenolic glucoside extracted from Gastrodia elata Blume, has been reported to play a protective role in some central nervous system -related diseases and is beneficial for the recovery of dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…G. elata has many pharmacological effects ( Wang et al., 2021b ; Zhou et al., 2021a ) and contains over 200 bioactive components and plant secondary metabolites, such as gastrodin (4-hydroxy methyl phenyl-β-D-glucopyranoside), gastrodigenin (p-hydroxybenzyl alcohol), p-hydroxybenzaldehyde, vanillin (4-hydroxy-3-methoxybenzaldehyde), parishin, G. elata polysaccharides, amino acids, and other compounds, which have been demonstrated to be the main components associated with the pharmacological activity of G. elata ( Yu et al., 2005 ; Kim et al., 2007 ; Chen et al., 2011b ). Among these, gastrodin and gastrodigenin are regarded as phytochemical indicators of G. elata in the Chinese pharmacopeia and are used in G. elata quality control ( Sun et al., 2023 ).…”
Section: Overview Of G Elata and Its Applicationsmentioning
confidence: 99%
“…G. elata has many pharmacological effects ( Wang et al., 2021b ; Zhou et al., 2021a ) and contains over 200 bioactive components and plant secondary metabolites, such as gastrodin (4-hydroxy methyl phenyl-β-D-glucopyranoside), gastrodigenin (p-hydroxybenzyl alcohol), p-hydroxybenzaldehyde, vanillin (4-hydroxy-3-methoxybenzaldehyde), parishin, G. elata polysaccharides, amino acids, and other compounds, which have been demonstrated to be the main components associated with the pharmacological activity of G. elata ( Yu et al., 2005 ; Kim et al., 2007 ; Chen et al., 2011b ). Among these, gastrodin and gastrodigenin are regarded as phytochemical indicators of G. elata in the Chinese pharmacopeia and are used in G. elata quality control ( Sun et al., 2023 ).…”
Section: Overview Of G Elata and Its Applicationsmentioning
confidence: 99%
“…In a separate study, Artusa et al reported that green coffee and roasted coffee extract can inhibit the effect of IRF 3, thereby inhibiting excessive IFN-β-induced inflammation [ 104 ]. Conversely, during viral infection, gastrodin (GTD) can promote the activation of IRF 3 in macrophages to facilitate the production of IFN-Is, resisting inflammation and anti-viral infection [ 105 ]. Another significant pathway for the production of IFN-Is through IRF 3 is cGAS/ STING signaling.…”
Section: Type I Interferon Signaling In Inflammationmentioning
confidence: 99%
“…It is highly contagious and zoonotic, frequently leading to vesicles and unclear on the tongue, papilla, or other positions. Although its morbidity is not so high, the injury is irreversible, then resulting in the enormous economic losses ( 1 , 2 ). VS is classified as a list B disease by Office International Des Epizooties (OIE), belonging to 1 of the 13 foreign diseases that need to be supervised in China.…”
Section: Introductionmentioning
confidence: 99%